MENJAGA HARMONI: MEMADUKAN BUDAYA MINAHASA (RITUAL KAMPETAN) DAN PRINSIP KEKRISTENAN DALAM KEHIDUPAN BER-JEMAAT - Kaensige, Mariska Theodora (PARADOSI: Jurnal Teologi Praktika, 2025)
This article explores the importance of religious moderation in harmonizing local culture, particularly the Kampetan ritual in Minahasa, with Christian principles. As a cultural heritage, the Kampetan ritual reflects values such as community solidarity, respect for ancestors, and togetherness. However, certain elements of the ritual, such as ancestor invocation, conflict with biblical teachings. Through religious moderation, positive cultural elements can be preserved and imbued with new meanings aligned with the Word of God. This approach includes transforming cultural symbols, such as the "watu" stone, reinterpreted as Christ the Cornerstone, and the red cloth symbolizing the blood of Christ. Churches play a crucial role in guiding congregations to understand, filter, and respect local traditions without compromising their faith principles. Furthermore, dialogue between traditional leaders and the church is essential to achieving harmony between tradition and faith. In conclusion, religious moderation offers a solution to balance local traditions and Christian faith. This approach not only preserves cultural identity but also enriches its meaning in the light of biblical truth, fostering harmony that strengthens faith and community unity.